KENDALA DAN UPAYA BADAN KEHORMATAN DEWAN DALAM MENJAGA KODE ETIK ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DI KABUPATEN SOLOK - Siska Permata Sari; Elsy Reni (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
The focus of study in this thesis is the Obstacles and Efforts of the Council's Ethics Council in Maintaining the Code of Ethics for Members of the Regional People's Representative Council (DPRD) in Solok Regency. The main problem in this thesis is a violation of the code of ethics committed by members of the DPRD of Solok Regency. Therefore the author is interested in examining what are the obstacles and efforts of the honorary body of the Solok Regency council in preventing violations of the code of ethics for DPRD members and how fiqh siyasa reviews the honorary body of the council in maintaining the code of ethics for DPRD members. This type of research is juridical-empirical research, namely field research. The sources of data in this thesis are the chairman and deputy chairman of the honorary body, members of the honorary body and 13 DPRD members. Data collection techniques that the authors use in this study are observations, surveys and interviews. The results of the research are, the constraints are family relationships, different educational backgrounds of DPRD members, meeting schedules that clash with party activities. Efforts made to socialize DPRD members regarding their duties and functions, provide education and training to improve skills and knowledge, independent honorary bodies on existing problems, approach the head of the faction. while the honorary body in the DPRD when viewed from the study of fiqh siyasa is equated with wilayatul al-madzalim because it has the same function, namely to supervise and guard so that leaders do not violate the provisions, and are obliged to take action if the leaders or authorities are proven to have committed an offense. Meanwhile, the difference is that the membership of the honorary body is entirely from the internal DPRD, while the members of the wilayatul al-madzalim institution are not bound by any institution.